Mechanical properties and thermal stability of ultrathin molybdenum nanowires. Issue 39 (1st April 2015) - Lin, Ken-Huang; Liao, Bo-Yuan; Ju, Shin-Pon; Lin, Jenn-Sen; Hsieh, Jin-Yuan
Abstract : The most stable structures of three ultrathin molybdenum (Mo) nanowires were predicted by the simulated annealing basin-hopping method (SABH) with the penalty algorithm. Abstract : The most stable structures of three ultrathin molybdenum (Mo) nanowires were predicted by the simulated annealing basin-hopping method (SABH) with the penalty algorithm. The predicted structures of Mo nanowires indicate that, at this small scale, they do not possess the BCC configuration found in bulk Mo material. Mechanical properties including the Young's modulus, yielding stress, and strength of these wires were determined by a tensile test after the analysis of the stress–strain profiles. In addition, in order to understand the feasibility of application of these Mo nanowires in nano-devices, their thermal stability was also investigated at room temperature (300 K) by MD simulation.